Saṃsāra meṃ naraka : yā Bībī ke lekcara - Salonavī, Amīna (Rāmakumāra-Presa-Bukaḍipo uttarādhikārī Navalakiśora-Presa-Bukaḍipo, 1956)
Satire auf das Familienleben in Indien. - Humorous narrative on husband-wife relations